Evolution-Based Clustering Technique for Data Streams with Uncertainty - Meesuksabai, Wicha; Kangkachit , Thanapat; Waiyamai, Kitsana (Agriculture and Natural Resources, 2012)
The evolution-based stream clustering method supports the monitoring and change detection of clustering structures. This paper presented HUE-Stream which extends E-Stream and E-Stream++ by introducing a distance function, cluster representation and histogram management for the different types of clustering structure evolution. Compared with UMicro and LuMicro, HUE-Stream produces higher clustering quality and is more robust over highly uncertain data streams; however, it requires longer processing time due to the fact that HUE-Stream detects change in the clustering structure evolution too frequently (in every round). To improve the processing time, proper periods of clustering structure evolution change detection were determined. With these proper periods, the processing time was greatly improved, while retaining the clustering quality. Compared to actual class of data in the KDDCup 1999 network intrusion detection dataset, a comparable number of clusters was obtained in all stream progressions.